A relação da maturação biológica com desempenho de membros superiores e inferiores de jovens atletas de voleibol - Rocha, Matheus de Lima (2023)
In volleyball, many factors can interfere with an athlete's performance, especially in the youth categories, where young athletes undergo various biological influences on their bodies. Among these influences, biological maturation stands out, and its relationship with the performance of upper and lower extremities is not well defined in the literature. In this regard, the objective of the present study was to analyze the relationship between biological maturation and the performance of young volleyball athletes. The study was cross-sectional and included a sample of 71 participants aged 8 to 14 years. Maturation was assessed by peak height velocity (PHV), and skeletal age was determined using the model proposed by Cabral. To assess anaerobic capacity, the Running-based Anaerobic Sprint Test (RAST) was used. The muscular power of the upper extremities was analyzed using the medicine ball throw test, and that of the lower extremities was evaluated through a vertical jump performed on a contact platform with an interruption system. After analyzing the results, the groups showed a relationship with anaerobic capacity between maturation stages in comparison to anaerobic power in RAST (EarlyPHV: 256.4; Circum-PHV: 171.3; Late-PHV: 105.7). The participants' fatigue index also showed a strong influence of maturation, indicating that more mature individuals had higher anaerobic capacity and were more prone to fatigue. Relative power was particularly pronounced in the upper extremities (Effect size: 1.5). There was a correlation between lean mass in the upper extremities and upper extremity power (r=0.73; P=0.001), and a weak correlation between lean mass and lower extremity power (r=0.30; P=0.2). The results lead to the conclusion that, when comparing different maturation stages, individuals with more advanced maturation exhibit greater anaerobic power, higher relative power in both upper and lower extremities, with a more significant influence on the upper extremities than on the lower extremities, and a stronger relationship with the fatigue index.